2012
DOI: 10.1186/1471-2172-13-60
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-finger nuclease mediated disruption of Rag1 in the LEW/Ztm rat

Abstract: BackgroundEngineered zinc-finger nucleases (ZFN) represented an innovative method for the genome manipulation in vertebrates. ZFN introduced targeted DNA double strand breaks (DSB) and initiated non-homologous end joining (NHEJ) after pronuclear or cytoplasmatic microinjection into zygotes. Resulting frame shift mutations led to functional gene ablations in zebra fish, mice, pigs and also in laboratory rats. Therefore, we targeted the rat Rag1 gene essential for the V(D)J recombination within the immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 50 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…There were no other developmental abnormalities noted in these animals, although the potential impact of developmental changes and/or alteration in other pathways in the absence of Rag1 protein is a limitation of this gene deletion approach. Qualitatively, the phenotypes observed in the present study are similar to those previously reported in Rag1-/-mice (18) and recently reported in the LEW/Ztm rat with ZFN-mediated disruption of Rag1 (29).…”
Section: Discussionsupporting
confidence: 92%
“…There were no other developmental abnormalities noted in these animals, although the potential impact of developmental changes and/or alteration in other pathways in the absence of Rag1 protein is a limitation of this gene deletion approach. Qualitatively, the phenotypes observed in the present study are similar to those previously reported in Rag1-/-mice (18) and recently reported in the LEW/Ztm rat with ZFN-mediated disruption of Rag1 (29).…”
Section: Discussionsupporting
confidence: 92%
“…The latter have a small, but nevertheless detectable, thymus (6) whereas three of the four mutant pigs lacked a thymus completely and the fourth had one that was extremely underdeveloped, as was also observed in pigs lacking an intact IL2RG gene (15,16). The lack of B and T cells is analogous to mouse, rat, and rare human RAG mutants (6,30,31), but, as with the porcine IL2RG knock-outs and human patients, RAG2…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, for mammalian species other than the mouse, genetic engineering was simply not possible due to an inability to derive legitimate ES cells despite considerable effort over many years. Recent advances in site-specific nuclease technologies (e.g ZFN, TALEN, CRISPR/Cas) are enabling direct, targeted deletion and targeted, sequential gene modifications via pronuclear injection of mouse embryos 10 and other species, including rat 11,12 . For genetic engineering, these technologies circumvent the need for ES cells.…”
Section: Derivation Of Mescsmentioning
confidence: 99%